Analisis Pengaruh Cues Terhadap Trust, Attitude, dan Online Shopping Intention di Instagram - Purnamaningrum, Larasati Chandra Githa; Alversia, Yeshika (UI Scholars Hub, 2021)
The purpose of this research is to determine the cues (signals/clues) in Instagram posts which are attractiveness, popularity and argument quality that can affect trust which will affect attitudes towards shopping using Instagram, and thus affect purchase intentions of Indonesian local beauty products through Instagram. The sample used in this study are active Instagram users aged 17 years and over who follow one of Indonesia’s local beauty brands in Instagram, and have not made purchases from the local beauty brand that they are followed. There were 226 respondents in this study and used pur- posive sampling. The research questionnaire was distributed online and used Partial Least Square- Structured Equation Modeling (PLS-SEM) to analyzed the data. The results of this study indicate that post popularity and argument quality can build trust in local beauty brand Instagram posts which then lead to attitude towards shopping using Instagram and purchase intention through Instagram. Meanwhile, post attractiveness does not affect trust in local beauty brand Instagram posts. Thus in this study it shows that consumers are more rely on cues from popularity and argument quality of Instagram posts to reduce uncertainty in shopping for local beauty products on Instagram.